PENGEMBANGAN BAHAN AJAR BERBANTUAN SOFTWERE MAPEL UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS MAHASISWA - Ummi Rosyidah; Astri Setyawati; Aulia Ar Rakhman Awaludin (Jurnal THEOREMS (The Original Research of Mathematics), 2021)
This research is a type of research and development which focuses on developing teaching materials for Basic Algebra courses which aim to improve understanding of mathematical concepts. Broadly speaking, the development model used in this study consists of 3 stages, namely the preliminary, development and evaluation stages. In the preliminary stage, the researcher conducted a literature study and analysis of course descriptions and identified teaching materials for Basic Algebra courses. The teaching materials developed are tested for validity, practicality and effectiveness. From the results of the module validation analysis, it was obtained 84.25 with good categories. The small scale trial obtained 38.7 with good category. The results of the analysis of the practicality of teaching materials during four meetings obtained an average score of 25.25 from the ideal score of 30 or 84.17 in the very good category. The result of the analysis of the effectiveness of the average score of the teaching profile of the lecturers using basic algebra teaching materials based on the maple-assisted scientific approach is 50.25 from the ideal score of 56 or 89.73% with the very good category. The average score of the learning activity profile of students who use basic algebra teaching materials based on the maple-assisted scientific approach is 44.5 from the ideal score of 52 or 85.58% in the very good category. From the analysis of the results of the test for understanding mathematical concepts, the total average is 0.58 with the moderate category, which can be concluded that the teaching materials for basic algebra courses with a scientific approach